1999
DOI: 10.1007/bf01257191
|View full text |Cite
|
Sign up to set email alerts
|

Generalized multi-resolution analyses and a construction procedure for all wavelet sets in ?n

Abstract: ABSTRACT. An abstract formulation t~'generalized multiresolution analyses is presented, and those GMRAs that come from multiwavelets are characterized. As an application of this abstract formulation a constructive procedure is developed, which produces all wavelet sets in Nn relative to an integral expansive matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 8 publications
0
153
0
Order By: Relevance
“…GMRAs were introduced in [4], and have since been studied in [5] and [3]; other authors had previously observed that much of the theory still works when we use Γ in place of the classical translation group Z n (see [1] and [9], for example).…”
Section: Multiplicity Functions and The Main Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…GMRAs were introduced in [4], and have since been studied in [5] and [3]; other authors had previously observed that much of the theory still works when we use Γ in place of the classical translation group Z n (see [1] and [9], for example).…”
Section: Multiplicity Functions and The Main Theoremmentioning
confidence: 99%
“…Ak and π is the representation determined by translation, the measure µ is necessarily absolutely continuous with respect to the Haar measure on the torus [4,Propositions 2 and 3]). This absolute continuity does not necessarily hold in general, but here we are interested in the converse, and we assume that our measures µ are absolutely continuous with respect to the Haar measure λ on Γ.…”
Section: Multiplicity Functions and The Main Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Before proceeding, we remark that the analysis of wavelets using the spectral multiplicity methods was begun by Baggett, Medina, and Merrill [2] in their study of generalized multiresolution analyses and MSF wavelets. Other spectral methods in the analysis of wavelets can be found in Jorgensen, et al in [7,20].…”
Section: Affine Quasi-affine and Weyl Heisenberg Framesmentioning
confidence: 99%
“…The multiplicity function is presented there as a complete invariant. Of course, in wavelet applications, there are also the additional consistency relations (see [BMM99]), but the notion of a multiplicity function is general.…”
Section: Unitary Operatorsmentioning
confidence: 99%